Cerebral Phaeohyphomycosis Due to Cladophialophora Bantiana in a Kidney Transplant Patient. (28th October 2020) - Yu, K; Devi, P; Pulinthanathu, R
Abstract: Casestudy : Phaeohyphomycosis is a group of infections caused by pigmented, black, dematiaceous fungi and is responsible for cutaneous, superficial and deep mycoses, disseminated infection and brain abscesses. The primary agents involved include Alternaria spp., Exophiala spp. and Cladophialophora spp. Cerebral phaeohyphomycosis is particularly devastating with mortality rates as high as 70-80%. These fungi are becoming increasingly important opportunistic pathogens in solid organ transplant recipients (SOTR). We report a case of cerebral phaeohyphomycosis in a 65-year-old male with living donor kidney transplant for four years and has been maintained on immunosuppressive therapy with tacrolimus and prednisone. The patient presented with aphasia, frontal headache, loss of peripheral vision of right eye, and mental status change for three months due to several left- sided parieto-occipital brain abscesses. Left occipital abscess resection and parietal partial lobectomy were performed to reduce intracranial hypertension and to remove abscesses. Histopathological evaluation revealed brain abscess with pigmented fungal organisms with elongated, branched and septate. The pus aspirated during surgical excision of brain lesions grew black mold, identified as Cladophialophora bantiana. The patient's neurological neurological condition had imporved after several weeks of combination antifungal therapy with posaconazole, liposomal amphotericin, and flucytosine. The lesions were initially suspected to be of tuberculous etiology, which was ruled out by histopathological examination. Such diagnostic dilemmas are common in the infection caused by Cladophialophora, which can cause treatment delay and death. Early diagnosis is therefore mandatory for the rapid treatment and survival of patients. As the number of SOTR increases, so does the incidence of fungal infections in that population. Surgery, along with antifungal therapy and a reduction in immunosuppression, are the cornerstones of treatment.